2022
DOI: 10.52403/ijhsr.20220312
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic Fatigue: A Concept Analysis

Abstract: Aim: This concept analysis aims to impart knowledge and recognize the pandemic fatigue of healthcare professional, especially nurses. The concept aims to identify the causes of pandemic fatigue to nurses, especially during the COVID-19 crisis. It also identifies the effect of pandemic fatigue on their productivity, their mental and physical aspect. It also analyzed the definitions of the concept via various case studies and researches like giving examples of the model, related, contrary and borderline cases. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…Pandemic fatigue was reported to be more common among younger people (42,46,50) and in cities that mandate mask wearing (49). As for occupation, a study in the Philippines identified that working as nurses posed a high risk of PF (53). Nurses are prone to developing pandemic fatigue due to their nature of work and the additional burden that COVID-19 has brought in.…”
Section: What Is the Prevalence Of Pandemic Fatigue In Many Countries...mentioning
confidence: 99%
See 1 more Smart Citation
“…Pandemic fatigue was reported to be more common among younger people (42,46,50) and in cities that mandate mask wearing (49). As for occupation, a study in the Philippines identified that working as nurses posed a high risk of PF (53). Nurses are prone to developing pandemic fatigue due to their nature of work and the additional burden that COVID-19 has brought in.…”
Section: What Is the Prevalence Of Pandemic Fatigue In Many Countries...mentioning
confidence: 99%
“…For instance, it can be prevented by following the established guidelines and support from the family and the nurses' institution. Furthermore, nurses can develop suitable strategies in order to curb fatigue (53).…”
Section: How Does the Government Overcome The Problem Of Pandemic Fat...mentioning
confidence: 99%